PENGARUH PENGEMBANGAN KARIR, MOTIVASI, DAN KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN PADA PT. CIOMAS ADISATWA KOTA BENGKULU - Firnanda, Friska Fera; Subandrio, Subandrio (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This type of quantitative descriptive research, the object of this research is employees at PT. Ciomas Adisatwa Bengkulu City. The Sampling method uses a non probability technique, namely accidental Sampling. The number of respondents in this study were 40 people. Data collection method using a questionnaire. Data analysis techniques using Multiple Linear Regression Analysis Test, and Hypothesis Test, namely t test and f test. The results of this study can be concluded that career development (X1) has a positive effect on employe performance (Y), Motivation (X2) has a positive effect on employee performance(Y), Emotional intelligence (X3) has a positive effect on employee performance (Y), Then career development (X1), Motivation (X2), Emotional intelligence (X3) together have a positive and significant effect on employee performance (Y). Keywords: Career development, Motivation, Emotional intelligence, and employee performance.